2014
DOI: 10.1089/vim.2014.0010
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response to Influenza A(H1N1)pdm2009 in Patients with Natural Infection and in Vaccine Recipients in the 2009 Pandemic

Abstract: The 2009 pandemic H1N1 mainly affected adolescents and children, and most of the elderly in Japan escaped clinical illness. To clarify the role of humoral immunity in the infection, the time kinetics of hemagglutination inhibition (HI), neutralization (NT), and IgG subclass antibody response directed against influenza A(H1N1)pdm2009 were analyzed in three consecutive specimens obtained from 51 young adults and children (group 1) who contracted pandemic influenza and from 74 pediatric clinic employees (group 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Several studies have shown that immunocompetent individuals are very likely to seroconvert (82%-95%) and to have seroprotective levels of HI antibodies (93%-98%) after natural influenza infection. [26][27][28][29] In the 31 One unexpected finding we observed was that lung transplant recipients seemed to seroconvert more frequently in response to influenza A infection compared to recipients of other organs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies have shown that immunocompetent individuals are very likely to seroconvert (82%-95%) and to have seroprotective levels of HI antibodies (93%-98%) after natural influenza infection. [26][27][28][29] In the 31 One unexpected finding we observed was that lung transplant recipients seemed to seroconvert more frequently in response to influenza A infection compared to recipients of other organs.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have shown that immunocompetent individuals are very likely to seroconvert (82%-95%) and to have seroprotective levels of HI antibodies (93%-98%) after natural influenza infection. [26][27][28][29] In the ------------------------------------------------------------------------------------------------------------------------------------------------------ Reciprocal hemagglutinin antibody titer at presentation p=0.39 Spearman`s rho = 0.12; p=0.27 immunocompromised setting, DhĂ©din et al compared the humoral immune response of 20 influenza A/H1N1pdm2009-infected allogeneic HSCT recipients with a cohort of HSCT recipients vaccinated with 2 doses of influenza A/H1N1pdm2009 vaccine. 30 The seroprotection rate after infection (60%) was within the range of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of adults and elderly persons might have affected the overall study outcome. In fact, adults were reported to lack IgG4 induction after vaccination 32 . Therefore, future studies evaluating IgE sensitization and immune responses to influenza vaccines should include adults and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, adults were reported to lack IgG4 induction after vaccination. 32 Therefore, future studies evaluating IgE sensitization and immune responses to influenza vaccines should include adults and the elderly. Second, the study was not designed to identify risk factors for vaccine‐induced anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus infection causes significant morbidity and occasional mortality in the solid organ transplant (SOT) population 1,2 . A key aspect of the immune response includes the development of antibodies directed against specific proteins within the influenza virus 3‐7 . Because of the immunosuppression required to avoid graft rejection, SOT recipients tend to have reduced antibody responses to both natural influenza infection and to vaccination 8,9 .…”
Section: Introductionmentioning
confidence: 99%